Integration of the ICD-11 and DSM-5 Dimensional Systems for Personality Disorders Into a Unified Taxonomy With Non-overlapping Traits - Gutiérrez, Fernando; Peri, Josep M.; Gárriz, Miguel; Vall, Gemma; Arqué, Estela; Ruiz, Laura; Condomines, Jaume; Calvo, Natalia; Ferrer, Marc; Sureda, Bárbara (Frontiers in Psychiatry, 2021)
The promise of replacing the diagnostic categories of personality disorder with a better-grounded system has been only partially met. We still need to understand whether our main dimensional taxonomies, those of the International Classification of Diseases 11th Revision (ICD-11) and the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM-5), are the same or different, and elucidate whether a unified structure is possible. We also need truly independent pathological domains, as they have shown unacceptable overlap so far. To inquire into these points, the Personality Inventory for DSM-5 (PID-5) and the Personality Inventory for ICD-11 (PiCD) were administered to 677 outpatients. Disattenuated correlation coefficients between .84 and .93 revealed that both systems share four analogous traits: negative affectivity, detachment, dissociality/antagonism, and disinhibition. These traits proved scalar equivalence too, such that scores in the two questionnaires are roughly interchangeable. These four domains plus psychoticism formed a theoretically consistent and well-fitted five-factor structure, but they overlapped considerably, thereby reducing discriminant validity. Only after the extraction of a general personality disorder factor (g-PD) through bifactor analysis, we could attain a comprehensive model bearing mutually independent traits.